A little bit of Sargassum goes a long way: seafloor observations of Sargassum fluitans and Sargassum natans in the Western Atlantic Ocean - Ashley Pries; Amanda N. Netburn; Heidi Batchelor; Victoria R. Hermanson (Frontiers in Marine Science, 2023)
The North Atlantic Ocean features high seasonal productivity of the brown seaweed Sargassum , which floats on the ocean surface and accumulates in large numbers in the Sargasso Sea. Sargassum blooms can stretch from the west coast of Africa to the Gulf of Mexico, and have created the largest seaweed blooms ever observed. Sargassum blooms have increased in intensity in recent years, and can negatively impact coastal communities when they wash up onshore in large quantities and decay. While seaweed sinking from surface waters to the seafloor may be an important carbon sink by removing carbon from the atmosphere, the magnitude of carbon sequestration by Sargassum and other macroalgae remains poorly understood. Given the magnitude of Sargassum blooms in the North Atlantic, they may pose a significant mechanism for carbon sequestration in the deep sea, though direct observations are rare. In this study, we documented the presence and distribution of Sargassum seaweed on the seafloor using video from ten remotely operated vehicle dives conducted on NOAA Ship Okeanos Explorer . Locations included sites in the Gulf of Mexico, in the Caribbean Sea, and off the Southeastern United States. Sargassum was observed in numbers ranging from 0 to over 112 per dive, and a frequency of between 0-11.23 observations for every 100 meters of horizontal distance. These observations suggest that Sargassum does make its way to the deep sea in potentially significant amounts. Natural systems like Sargassum sinking could serve as natural laboratories for understanding and managing seaweed burial as a climate mitigation strategy. Long-term monitoring of the fate of sunken Sargassum on the seabed is needed in order to determine how much is ultimately sequestered rather than recycled back into the system. Such observations would inform the feasibility of Sargassum farming and/or facilitated sinking as potential carbon dioxide removal strategies.

An initial ecological characterization of mesopelagic fauna at Johnston Atoll and Musicians Seamounts - Jason Gronich; Adrienne Copeland; Michael Ford; Amanda N. Netburn (Regional Studies in Marine Science, 2023)

One byte at a time: gathering best practices, guidelines, and resources for data standards to support ocean exploration and characterization - Kasey Cantwell; Amanda W. J. Demopoulos; Mitchell G. Hebner; Rachel Medley; Mark Mueller; Amanda N. Netburn (Frontiers in Marine Science, 2023)
Initiated through Presidential direction and now codified, the National Ocean Mapping, Exploration, and Characterization (NOMEC) Council comprises leaders from U.S. federal agencies with a shared goal of mapping all waters of the United States and exploring and characterizing priority areas. The NOMEC Council’s two Interagency Working Groups, Ocean and Coastal Mapping (IWG-OCM) and Ocean Exploration and Characterization (IWG-OEC), both achieved major milestones recently with the 2023 release of the Draft Standard Ocean Mapping Protocols (SOMP) and the 2022 publication of the National Priorities for Ocean Exploration and Characterization. Building on this groundwork, the IWG-OEC is now looking to define and share best practices, guidelines, and resources for ocean exploration and characterization with the long-term goal of increasing community wide standardization to help achieve consistent common practices. First, the IWG-OEC plans to compile federal agency resources and share them in a newly developed online resource repository. The next phase is for the IWG-OEC to create opportunities for non-federal sectors to provide input on developing and populating this repository with additional content (existing standards and protocols, best practice and guidelines documents, etc.). After experts representing multiple sectors are identified, a series of results-oriented workshops are planned to provide input on all aspects of the data, products, and services from exploration and characterization. Finally, the IWG-OEC plans to widely share the online repository of best practices and standard operating procedures. A systematic, transparent, and collaborative process to share standards and protocols can help to enhance the interoperability of data and inform new lines of inquiry, discovery, research, and innovation.

Distributions of the Pelagic Holothurian Pelagothuria in the Central Pacific Ocean as Observed by Remotely-Operated Vehicle Surveys - Gina M. Selig; Amanda N. Netburn; Mashkoor Malik (Frontiers in Marine Science, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Hydrothermal Vents and Methane Seeps: Rethinking the Sphere of Influence - Lisa A. Levin; Amy R. Baco; David A. Bowden; Ana Colaco; Erik E. Cordes; Marina R. Cunha; Amanda W. J. Demopoulos; Judith Gobin; Benjamin M. Grupe; Jennifer Le; Anna Metaxas; Amanda N. Netburn; et al. (Frontiers in Marine Science, 2016)

Deepwater Horizon Oil Spill: A Review of the Planktonic Response - Raffaela Abbriano; Magdalena Carranza; Shane Hogle; Rachel Levin; Amanda Netburn; Katherine Seto; Stephanie Snyder; Peter Franks (Oceanography, 2011)